2019
DOI: 10.3390/ani9050252
|View full text |Cite
|
Sign up to set email alerts
|

Using Qualitative Methods to Explore Farrier-Related Barriers to Successful Farriery Interventions for Equine Welfare in India

Abstract: Farriery is a critical component of healthcare services for working equids. However, in India, an informal workforce, lack of structured training facilities and non-implementation of farriery regulations pose challenges for quality farriery. Brooke India, an equine welfare organisation, has undertaken many initiatives aiming to improve farriery services, including technical training and engagement with equid-owning communities. However, this has met with varying success. The study aimed to identify factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…To date, the Behaviour Change Wheel and associated theories have been utilised to varying extents in a number of animal welfare and farmer behaviour change studies. For example, Mohite et al (2019) [65] examined barriers to technical competence in Indian farriers via focus groups. Mohite et al (2019) [65] concluded that due to unwillingness of horse owners to pay for a good service and a low motivation in the farriers for training, behaviour change interventions should target Opportunity and Motivation.…”
Section: Application Of Behavioural Science Theory In Animal Welfamentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the Behaviour Change Wheel and associated theories have been utilised to varying extents in a number of animal welfare and farmer behaviour change studies. For example, Mohite et al (2019) [65] examined barriers to technical competence in Indian farriers via focus groups. Mohite et al (2019) [65] concluded that due to unwillingness of horse owners to pay for a good service and a low motivation in the farriers for training, behaviour change interventions should target Opportunity and Motivation.…”
Section: Application Of Behavioural Science Theory In Animal Welfamentioning
confidence: 99%
“…For example, Mohite et al (2019) [65] examined barriers to technical competence in Indian farriers via focus groups. Mohite et al (2019) [65] concluded that due to unwillingness of horse owners to pay for a good service and a low motivation in the farriers for training, behaviour change interventions should target Opportunity and Motivation. However, the focus group discussions did not appear to have been shaped around the COM-B model and the model was referred to only once, in the discussion section of the paper.…”
Section: Application Of Behavioural Science Theory In Animal Welfamentioning
confidence: 99%
“…As a result, many NGOs are broadening the scope of their programming to target human factors and more actively engage with the people responsible for determining animal welfare. Approaches include introducing knowledge and skills to communities and helping to develop local infrastructure in order to support sustainable welfare improvements [14]. Increasing owner knowledge about animal welfare and sentience through targeted education programmes…”
Section: Introductionmentioning
confidence: 99%
“…Different models and approaches have been employed by different NGOs over time, and vary depending upon the size and philosophy of the organisation, the areas of the world in which they work and their funding sources [13]. These initiatives include the use of participatory methods [14], educational programmes for school children [15], advocacy [16], the provision of access to free veterinary treatment [10,[17][18][19], providing technical training and skills in fields such as farriery and saddlery to individuals in equid owning communities [20,21], and initiatives that target specific aspects of welfare such as handling and behaviour [22] or lameness [23]. There is debate surrounding the efficacy of the range of welfare initiatives that are implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Veterinary treatment is often offered for a short period of time with specialist equipment and drugs transported for this purpose but after withdrawal, lack of existing animal health infrastructure and inability to follow up cases can prevent long term welfare improvement [ 4 ]. It has also been highlighted that purely service based approaches are likely to be treating the symptoms rather than the root causes of welfare problems [ 20 , 24 ]. The creation of dependency on free service provision is also a concern when services are likely to, at some point, be withdrawn [ 13 ].…”
Section: Introductionmentioning
confidence: 99%